MMP2 and MMP9 are Associated with Apical Periodontitis Progression and Might be Modulated by TLR2 and MyD88 - Barreiros,Driely (2018)
Abstract The aim of this study was to evaluate the expression of MMP2 and MMP9 during apical periodontitis (AP) progression in TLR2 (TLR2 KO) and in MyD88 (MyD88 KO) knockout mice compared to wild type (WT) mice. AP was induced in mandibular first molars of TLR2 KO (n= 18), MyD88 KO (n= 18), and WT mice (n= 18). After 7, 21, and 42 days, the animals were euthanized and the jaws were dissected and subjected to histotechnical processing. Subsequent sections were stained by immunohistochemistry and evaluated for detection of MMP2 and MMP9. Statistical analysis of the semi-quantitative analysis of immunohistochemistry was performed using chi-square test (α = 0.05). In the initial periods of AP progression, an increased expression of MMP9 in the TLR2 KO and MyD88 KO mice was observed. In the final periods of AP progression, a reduction of MMP2 expression and an increase of MMP9 expression in the TLR2 KO mice were observed. MMP2 and MMP9 production was modulated for TLR2 and MyD88 during apical periodontitis progression.